Characteristics Fenotip of Vermiculated Spinefoot (Siganus vermiculatus Valenciennes, 1835) in Pangkajene and Island Waters Makassar Strait - Amran, Amran; Kantun, Wayan; Latif, Nursidi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The use of vermiculated spinefoot has been carried out intensively so that it is suspected to have caused phenotypic changes. The objective of research to identify phenotypic characteristics which include morphometrics and meristics. This research was conducted February to April 2022 using a survey method in the Pangkep waters of the Makassar Strait. The samples identified were 45 individuals from five places namely the islands of Sabangko, Salemo, Sagara, Bangko-Bangkoang and Laiya. Each island identified nine fish with representation of small, medium and large sizes. Identification of morphometric characteristics was carried out on 29 parameters, while meristic characteristics on the number of strong and weak rays of the dorsal, pectoral, abdominal and anal fins. Data were analyzed using principal components and cluster analysis. The results showed that the main and very strong characteristics of the vermiculated spinefoot from the five sampling locations were anal fin base length, pelvic fin base length, head length and head width, the length of the longest anal fin rays for all sizes. The morphometric characteristics of the five islands obtained varied conditions with two morphometric groups namely the small and medium size vermiculated spinefoot fish group and the large vermiculated spinefoot fish group. The meristic characteristics of the dorsal, pectoral, pelvic and anal fins of the five islands are relatively the same. Based on the morphometric characteristics, vermiculated spinefoot fish should be managed separately, namely small and medium sized fish with the same management model, while large sized fish should be managed separately.